Congenital constriction ring syndrome of the limbs: A prospective study of 16 cases - Adu Emmanuel; Annan Charles (Wolters Kluwer Medknow Publications, 2008)
Background: The congenital constriction ring syndrome is characterised by fibrous bands that encircle, strangle and even amputate parts of the foetus. It is a common condition amongst Ghanaian patients, but data on it is quite scanty. Materials and Methods: A prospective study of patients presenting at a plastic surgical clinic in Ghana with the characteristics of the congenital constriction ring syndrome was undertaken. The patients were examined clinically and the findings recorded. An x-ray and clinical photograph of the affected limbs was taken. Treatment required several staged operations. Surgical correction of the constriction ring was done by excision and Z-plasty to prevent or alleviate lymphoedema, separation of distally fused digits and skin grafting of defect. Results: Sixteen patients made up of 10 males and six females were seen. The age at presentation ranged from nine days to 12 years with a mean age of 14.6 months. Twenty-two limbs were affected, made up of four right upper limbs, six left upper limbs, seven right lower limbs and five left lower limbs. In the upper limb malformations involved 42 digits; in the lower limb malformations involved 33 toes, one foot and five legs. Four main types of lesions were found: constriction rings, intrauterine amputations, acrosyndactyly, and simple syndactyly. Conclusion: Congenital constriction ring syndrome is of uncertain aetiology and could cause morbidity in the newborn. The syndrome and its complications are amenable to corrective surgery with good results. Early intervention is desirable for a successful outcome.